(untitled) (Scientific journal of the Fergana State University, 2025)
The article examines the speech act of apology from the perspective of linguoculturology. It analyzes the key components of apologies, their functions, and strategies in various cultures, including Russian, English, Japanese, and Uzbek. Special attention is paid to the influence of cultural values on the linguistic features of apologies. The results of the study can be useful in the fields of intercultural communication, translation studies, and language teaching.